IKAN SERIBU NAMA DALAM KRIYA KULIT - Yus Maryo (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2014)
“Seribu Nama” or ‘thousand name’ fish is another name for arwana. There are four kinds of a thousand name fish (arwana), which are: super red, golden, silver, and silver red. Super red is the most expensive one, besides, Seribu Nama Fish (arwana) has a mystery which is called a good luck or magic power, good fortune, reducing the devil, and giving the signal of the lucky. That is why it is chosen as an idea in the leather craft because of the value in the seribu nama fish (arwana), especially in its shape, the movement of its parts of the body: fin, the head of the fin, and its tail which completes it. The process in the manufacturing of the craft includes three stages; the first is the exploration including the exploration of the source of idea and data gathering, the second is planning, it is the sketch making until the best design selecting, the third is the step by step making until the work is done. The manufacturing is started by the preparing material and equipment, the pattern making, the making of work frame, the cutting of solid heart sponge, the gluing and assembling, the shaping of the leather skin, the glass setting, the cartoon setting and laken cloth, the hole making, and the plaiting. The research processes started from the idea of a seribu nama fish (arwana), and through the process of manufacturing that is done, finally it is made the leather craft in two dimensions. The shape of the craft emphasizes more to the craftsmanship and expression, and has the meaning or message that is intended to be conveyed by the writer.